Knowledge management in the public sector: a bibliometric analysis - Câmara, Kathiurcia Montovanelli Cazotti (2021)
Knowledge Management can contribute a lot to the success of organizations, both public and private. However, these have realized this for a long time and have been successful in actions that seek to manage knowledge, while those, have made use of this instrument more recently. Tacit knowledge, derived from the personal experience of employees of any organization, is a key element, and is sometimes lost, especially in the public sector, marked by constant changes in staff. It is essential to convert this knowledge into explicit knowledge, so that it is available and can be accessed by those who are competent. This article aims to conduct a study on publications that refer to knowledge management in the public sector, in order to answer the following question: what instruments and methods have been used by the public sector to convert tacit knowledge into explicit knowledge? The methodological proposal of the study was to carry out a research with bibliometric and qualitative analysis, in articles searched in the Web of Science database. The results of the study show that among the main instruments and methods used to convert tacit knowledge into explicit knowledge, the use of documents, programs and systems that enable the organization and availability of knowledge, facilitating its access, stands out. It was concluded that despite the recognition of the importance of knowledge management by literature, concrete initiatives for its implementation in the public sector are still timid, with room for innovation.